Impact of Family-Work Conflicts on Job Withdrawal Behavior of College Teachers - S. Sangeetha; Dr. S. K. Nagarajan (Revista Electronica de Veterinaria, 2024)
Conflicts may occur in the family structure that individuals will face in the course of the life cycle and the work life that individuals endeavor to sustain their lives. Individuals’ work lives typically become more complicated, and increased job responsibilities may affect family life. Generally teachers' withdrawal behavior in colleges is due to job stress and random interruptions in work due to family-work conflicts. Hence, the research tries to identify the impact of family-work conflicts on job withdrawal behaviour of college teachers. It is demonstrated that the work-family conflict significantly influence job stress among college teachers.  The research found that the family-work conflict significantly influence job stress among college teachers. It is found that the work-family conflict significantly influence withdrawal behaviour among college teachers. The analysis demonstrated that the job stress significantly influence withdrawal behaviour among college teachers. Hence, it is concluded that College teachers must anticipate individual moods and student-related stress to avoid increasing their stress levels. This can reduce their withdrawal behaviors.